O comércio de suplementos alimentares na cidade de Rio Claro - SP: análise dos fatores locacionais e de consumo - Rosa, Micaela Bandeira [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The objective of this research was to analyze the locational factors of the trade of food supplements in stores specializing in the sale of these products in the city of Rio Claro, 170km away from the capital of São Paulo, addressing locational aspects of the trade, as well as the reasons for the consumption of food supplements (a product that contains vitamins and/or minerals added to complement food). Thus, supplements provide positive effects on the human body and greater performance in performing physical activities (GOMES & TERAPEGUI, 2000). The food regime is linked to international production relations, intensive research and the growing stimulus to consumerism. It is necessary, then, to understand the locational dynamics of commercial establishments and contemporary diets, as well as their spatial juxtaposition. Semistructured interviews were carried out with the owners of food supplement stores, seeking to elucidate the locational factors responsible for the spatial pattern of the supplement stores in the city, as well as the reasons that have led to the increased consumption of food supplements, whether for quality of life or consumption fast and/or for aesthetic desire. Commercial activity and its locational factors can show us how the territory also serves as a “commodity”. Understanding the locational aspects of these businesses and the consumption of their products encompass elements of a social nature, urban geography and spatial distribution.

O objetivo da presente pesquisa, consistiu em analisar os fatores locacionais comércio de suplementos alimentares nas lojas especializadas em vendas destes produtos na cidade de Rio Claro, distante 170km da capital de São Paulo, abordando aspectos locacionais do comércio, bem como as razões do consumo de suplementos alimentares (produto que contém vitaminas e/ou minerais adicionados no intuito de complementar uma alimentação). Dessa forma, os suplementos proporcionam efeitos positivos no organismo humano e maior desempenho na realização de atividades físicas(GOMES & TERAPEGUI, 2000). O regime alimentar está ligado às relações internacionais de produção, pesquisas intensivas e ao crescente estímulo ao consumismo. É necessário, então, entender a dinâmica locacional dos estabelecimentos comerciais e os regimes alimentares contemporâneos, como também, sua justaposição espacial. Foram realizadas entrevistas semiestruturadas com os proprietários de lojas de suplementos alimentares, buscando elucidar os fatores locacionais responsáveis pelo padrão espacial das lojas de suplementos no município, bem como as razões que tem levado ao aumento consumo dos suplementos alimentares, seja pela qualidade de vida, consumo rápido e/ou pelo desejo estético.A atividade comercial e seus fatores locacionais podem nos mostrar como o território também serve como “mercadoria”. Entender os aspectos locacionais desses comércios e o consumo de seus produtos abrangem elementos de natureza social, da geografia urbana e distribuição espacial.
The food supplement trade in the city of Rio Claro - SP: analysis of locational and consumption factors
Keywords: Location factors; Business; Food suplements; Fatores locacionais; Comércio; Suplementos alimentares